2011
DOI: 10.1111/j.1708-8240.2011.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Abfraction, Abrasion, Biocorrosion, and the Enigma of Noncarious Cervical Lesions: A 20‐Year Perspective

Abstract: By performing a comprehensive medical and dental history, using precise terms and concepts, and utilizing the Revised Schema of Pathodynamic Mechanisms, the dentist may successfully identify and treat the etiology of root surface lesions. Preventive measures may be instituted if the causative factors are detected and their modifying factors are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
206
1
139

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(351 citation statements)
references
References 74 publications
(152 reference statements)
5
206
1
139
Order By: Relevance
“…Noncarious Cervical Lesions (NCCLs) are characterized by hard tissue loss in the cement-enamel junction (CEJ) [1][2][3][4]. NCCLs are commonly found in dental practice, with prevalence rates up to 85% [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncarious Cervical Lesions (NCCLs) are characterized by hard tissue loss in the cement-enamel junction (CEJ) [1][2][3][4]. NCCLs are commonly found in dental practice, with prevalence rates up to 85% [5].…”
Section: Introductionmentioning
confidence: 99%
“…NCCLs are commonly found in dental practice, with prevalence rates up to 85% [5]. The origin and progression of theses lesions are related to three etiological factors: stress (tensile/compressive stress concentration), biocorrosion (acid-induced dentin chemical degradation) and friction (attrition and abrasion) [2,6]. Although there is no consensus regarding the diagnostic and management of NCCLs, the knowledge of multifactorial etiology is important to prevent more aggressive dental structure damage (Figure 1) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our results approach those of Oginni, et al [13] which in its study on 106 Nigerian patients found a prevalence of 37.7% of abfraction. Several studies tried to correlate these lesions with factors etiologic [2,4,6,8,[10][11][12]. A study was conducted by Faye, et al [14] on a non toothbrushing population with Hansen's disease (leprosy).…”
Section: Sociodemographics Conditionsmentioning
confidence: 99%
“…Following the introduction of the term abfraction by Grippo [7], to represent the microfracture of tooth substance in areas of stress concentration, the term remains misconstrued and misused Published studies have demonstrated the effects of stress combined with acids and enzymatic proteases as being factors in the genesis of NCCLs. Unfortunately, the term abfraction has become a "buzzword, " implying a single etiology, and is frequently used erroneously to designate all NCCLs [8]. The clinician should consider all etiologic and modifying factors before completing the diagnosis or initiating treatment if indicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation